EFFECTIVENESS OF RHEUMATIC EXERCISES IN REDUCING JOINT PAIN IN ELDERLY PEOPLE SUFFERING FROM RHEUMATOID ARTHRITIS - Permata Sari, Pera; Andre Utama Saputra; Sasono Mardiono; M. Romadhon (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Rheumatoid arthritis or better known as rheumatism is a progressive autoimmune disease with chronic inflammation that attacks the musculoskeletal system but can involve organs and body systems as a whole. This study aims to determine the effectiveness of rheumatic exercises on changes in joint pain in elderly people with rheumatoid arthritis. This research is a type of experimental research using a pre-experimental design research method using a one group pre and post test design approach. The sample in this study was 30 respondents, sampling used total sampling technique. Collecting primary data by observing the pain scale of respondents as a measuring tool. Data processing using a computer through the SPSS for Windows version 16 program with the Wilcoxon paired statistical test with a significance level of α = 0.05 and obtained a value of p = 0.000 which means p < α. This shows that Ha was accepted and Ho was rejected, meaning that there is effectiveness of rheumatic exercise on changes in joint pain in elderly people with rheumatoid arthritis at the Harapan Kita Social Home, Palembang City in 2024.